2014
DOI: 10.1126/scitranslmed.3010189
|View full text |Cite
|
Sign up to set email alerts
|

Visnagin protects against doxorubicin-induced cardiomyopathy through modulation of mitochondrial malate dehydrogenase

Abstract: Doxorubicin is a highly effective anti-cancer chemotherapy agent, but its usage is limited by its cardiotoxicity. To develop a drug that prevents the cardiac toxicity of doxorubicin while preserving its anti-tumor potency, we established a doxorubicin-induced cardiomyopathy model in zebrafish that recapitulated the cardiomyocyte apoptosis and contractility decline observed in patients. Using this model, we screened 3000 compounds and discovered that visnagin (VIS) and diphenylurea (DPU) rescue cardiac performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 43 publications
3
100
0
2
Order By: Relevance
“…We previously reported that C1 binds to mitochondrial malate dehydrogenase (MDH2) and postulated that modulation of MDH2 may be responsible for the cardioprotective effect of C1 (12). However, we have found manipulation of this pathway for therapeutic purposes to be challenging, given the importance of MDH2 in maintaining normal mitochondrial metabolism and bioenergetics.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…We previously reported that C1 binds to mitochondrial malate dehydrogenase (MDH2) and postulated that modulation of MDH2 may be responsible for the cardioprotective effect of C1 (12). However, we have found manipulation of this pathway for therapeutic purposes to be challenging, given the importance of MDH2 in maintaining normal mitochondrial metabolism and bioenergetics.…”
Section: Discussionmentioning
confidence: 92%
“…As oxidative stress has been reported as a key mechanism of DOX-induced cardiotoxicity, we previously assessed hydrogen peroxide (H 2 O 2 ) levels in cultured cardiomyocytes (12). DOX treatment was associated with an increase in H 2 O 2 levels that was not affected by the addition of C1.…”
Section: Determination Of Sar In Zebrafishmentioning
confidence: 99%
See 3 more Smart Citations